2015
DOI: 10.1002/2014jd022970
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of black and brown carbon multiple‐wavelength‐dependent light absorption from biomass and fossil fuel combustion source emissions

Abstract: Quantification of the black carbon (BC) and brown carbon (BrC) components of source emissions is critical to understanding the impact combustion aerosols have on atmospheric light absorption. Multiple-wavelength absorption was measured from fuels including wood, agricultural biomass, coals, plant matter, and petroleum distillates in controlled combustion settings. Filter-based absorption measurements were corrected and compared to photoacoustic absorption results. BC absorption was segregated from the total li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 70 publications
(76 reference statements)
8
113
1
Order By: Relevance
“…The patterns of the wavelength-dependent responses shown in Fig. 1 were consistent with the findings from several previous studies, which suggested that UV absorbing compounds are enriched in biomass-combustion PM but scarce in diesel PM (Chen et al, 2015;Olson et al, 2015) or traffic-related PM (Kirchstetter et al, 2004). Broadly, the light-absorbing organic compounds, referred to as "brown carbon" or BrC, have been shown to strongly absorb UV (Andreae and Gelencsér, 2006).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The patterns of the wavelength-dependent responses shown in Fig. 1 were consistent with the findings from several previous studies, which suggested that UV absorbing compounds are enriched in biomass-combustion PM but scarce in diesel PM (Chen et al, 2015;Olson et al, 2015) or traffic-related PM (Kirchstetter et al, 2004). Broadly, the light-absorbing organic compounds, referred to as "brown carbon" or BrC, have been shown to strongly absorb UV (Andreae and Gelencsér, 2006).…”
Section: Introductionsupporting
confidence: 89%
“…Studies show that woodsmoke enhancement peaks at ∼ 300 nm (Kirchstetter et al, 2004;Kirchstetter and Thatcher, 2012). It is possible that including shorter wavelengths in future instrumentation would improve the sensitivity to woodsmoke PM (Olson et al, 2015). Another approach taking advantage of UV enhancement (or wavelength dependence of the aerosol absorption coefficient in general), as reported by Sandradewi et al (2008a), derives light absorption Ångström exponents (AAE, or α) from multi-wavelength Aethalometer readings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential sources of BrC include emissions from biomass burning (Kirchstetter et al, 2004;Moosmüller et al, 2009;Chen and Bond, 2010;Lack et al, 2012a;Saleh et al, 2014;Washenfelder et al, 2015); incomplete combustion of fossil fuels, especially coal (Bond, 2001;Yang et al, 2009;Olson et al, 2015); and secondary organic aerosols (Saleh et al, 2013;Zhang et al, 2013;Lin et al, 2015). There exists significant uncertainty concerning the relative contribution of each of these source types to total BrC concentrations, but several studies have identified biomass burning as a potentially significant source (Washenfelder et al, 2015;McMeeking et al, 2014;Lack et al, 2012a).…”
mentioning
confidence: 99%
“…(c) the Ångström absorption exponent of BC (α BC ) is assumed a priori. In this work α BC = 1 was set according to expectancies for pure, small BC spheres (e.g., [3]) as often applied in the literature (e.g., [51]). Nevertheless, different choices can be in principle be performed due to the possible effect of BC core and coating sizes on the Ångström absorption exponent (e.g., [52]).…”
Section: Optical Source and Component Apportionment: The Multi-wavelementioning
confidence: 99%